"Tanahku Indonesia": On Materialscape as the Materiality of a Nation. Issue 2 (2nd April 2020) - Atmodiwirjo, Paramita; Yatmo, Yandi Andri
Abstract: This paper explores how the architectural exhibition "Tanahku Indonesia" used architectural materiality to represent the cultural diversity of Indonesia. The exhibition reframed the idea of materiality using the perspective of materialscape as an extended view of material; a view that encompassed the contexts and origins, as well as the diverse production processes behind physical materiality. In particular, this paper highlights the curatorial practices and how they engaged with and highlighted the nation's cultural diversity. The exhibition was an act of resistance against the universalizing forces of the modern construction industry. This article explores the integrated approach to research, collection and production that the curators developed and how they demonstrated the critical role of exhibitions and curatorial practice in advancing the discourse on local materiality and the sustainability of culture and tradition.